Fuel Usage Towards UINSU Tuntungan Campus using Greedy Algorithm - Alfarizi, Muhammad; Hasugian, Abdul Halim (Sistemasi: Jurnal Sistem Informasi, 2024)
Universitas Islam Negeri Sumatera Utara (UINSU) is one of the growing higher education institutions in Tuntungan, Medan. As a university that continues to improve the quality of education and facilities for its students. Inefficient use of fuel can lead to waste of resources, increased operational costs, as well as a negative impact on the environment. This research aims to develop and implement greedy algorithm in determining efficient travel routes for students, lecturers, and administrative staff to UINSU Tuntungan campus. The results showed that the Greedy algorithm proved effective in determining the shortest route between several points, the test results showed that this application was able to generate the optimal route quickly. Users can easily determine the shortest path and estimate fuel requirements for travel to campus so that this application is very helpful in efficient travel planning.